2021
DOI: 10.1016/j.stem.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Development of the Human Intestinal Niche at Single-Cell Resolution

Abstract: Highlights d Cell diversity in the developing human intestine was interrogated using scRNA-seq d PGDFRA HI /F3 HI /DLL1 HI mesenchyme lines the epithelium and expresses NRG1 d EGF, a common in vitro niche factor, is not abundant in the crypt domain d Compared with EGF, NRG1 increases cellular diversity in enteroid culture

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(135 citation statements)
references
References 67 publications
8
127
0
Order By: Relevance
“…A developing human multi-organ cell atlas identifies organ-specific features We established a developing human multi-organ reference cell atlas focusing on endoderm-derived organs by integrating newly generated and published single-cell (sc) transcriptomes from lung, esophagus, liver, stomach, small intestine (duodenum, jejunum, and ileum), and colon (155,232 cells in total) with an age distribution from 7-21 post-conception weeks (PCWs) (Figure 1A; Tables S1 and S2; key resources table; Holloway et al, 2020Holloway et al, , 2021Miller et al, 2020). We integrated all of the developing human scRNA sequencing (scRNA-seq) data using cluster similarity spectrum (CSS) (He et al, 2020) to correct for batch effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A developing human multi-organ cell atlas identifies organ-specific features We established a developing human multi-organ reference cell atlas focusing on endoderm-derived organs by integrating newly generated and published single-cell (sc) transcriptomes from lung, esophagus, liver, stomach, small intestine (duodenum, jejunum, and ileum), and colon (155,232 cells in total) with an age distribution from 7-21 post-conception weeks (PCWs) (Figure 1A; Tables S1 and S2; key resources table; Holloway et al, 2020Holloway et al, , 2021Miller et al, 2020). We integrated all of the developing human scRNA sequencing (scRNA-seq) data using cluster similarity spectrum (CSS) (He et al, 2020) to correct for batch effects.…”
Section: Resultsmentioning
confidence: 99%
“…Integrating HIO and primary duodenum data unveils transient cell states during human intestine mesenchyme development Mesenchymal-epithelial signaling regulates the emergence of crypt-villus architecture during development and maintains crypt homeostasis after villus formation (Holloway et al, 2021;Kinchen et al, 2018;McCarthy et al, 2020a;Santos et al, 2018;Shoshkes-Carmel et al, 2018;Smillie et al, 2019). To study intestine mesenchyme development, we first annotated cell clusters in the developing human duodenal mesenchyme (Figure S4A; Data S1).…”
Section: Mapping To a Multi-organ Reference Atlas Reveals The Fidelity Of Human Intestinal Organoidsmentioning
confidence: 99%
“…Recent scRNA-seq studies have identified diversity in cell types and states within epithelial, mesenchymal, and immune cells of the adult intestine (Kinchen et al, 2018;Martin et al, 2019;Parikh et al, 2019;Smillie et al, 2019). In many cases, their origins, role, and timing in development remain unclear; however, ongoing work is beginning to address this using unbiased, highthroughput methods (Elmentaite et al, 2020;Holloway et al, 2020) and expanding on earlier smaller scale studies (Gao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Human intestinal enteroids (HIEs) are patient-derived endoderm-only 3D structures composed of heterogeneous cell populations recapitulating intestinal tissues in vivo, providing a more faithful experimental model than immortalized and transformed cells. A large degree of epithelial cellular diversity is observed in HIEs: Columnar intestinal epithelial, stem/progenitor, enteroendocrine, and secretory cells can be observed depending on the culture conditions [6]. Spheroid structures can also be transitioned into 2D monolayers to facilitate host-microbe interaction studies in physiologic asymmetric oxygen conditions [7].…”
Section: Introductionmentioning
confidence: 99%